Human Herpesvirus 8 Interferon Regulatory Factor-Mediated BH3-Only Protein Inhibition via Bid BH3-B Mimicry - Choi, Young Bong (Public Library of Science, 2012)
Viral replication efficiency is in large part governed by the ability of viruses to counteract pro-apoptotic signals induced by infection of host cells. For HHV-8, viral interferon regulatory factor-1 (vIRF-1) contributes to this process in part via inhibitory interactions with BH3-only protein (BOP) Bim, recently identified as an interaction partner of vIRF-1. Here we recognize that the Bim-binding domain (BBD) of vIRF-1 resembles a region (BH3-B) of Bid, another BOP, which interacts intramolecularly with the functional BH3 domain of Bid to inhibit it pro-apoptotic activity. Indeed, vIRF-1 was found to target Bid in addition to Bim and to interact, via its BBD region, with the BH3 domain of each. In functional assays, BBD could substitute for BH3-B in the context of Bid, to suppress Bid-induced apoptosis in a BH3-binding-dependent manner, and vIRF-1 was able to protect transfected cells from apoptosis induced by Bid. While vIRF-1 can mediate nuclear sequestration of Bim, this was not the case for Bid, and inhibition of Bid and Bim by vIRF-1 could occur independently of nuclear localization of the viral protein. Consistent with this finding, direct BBD-dependent inactivation by vIRF-1 of Bid-induced mitochondrial permeabilization was demonstrable in vitro and isolated BBD sequences were also active in this assay. In addition to Bim and Bid BH3 domains, BH3s of BOPs Bik, Bmf, Hrk, and Noxa also were found to bind BBD, while those of both pro- and anti-apoptotic multi-BH domain Bcl-2 proteins were not. Finally, the significance of Bid to virus replication was demonstrated via Bid-depletion in HHV-8 infected cells, which enhanced virus production. Together, our data demonstrate and characterize BH3 targeting and associated inhibition of BOP pro-apoptotic activity by vIRF-1 via Bid BH3-B mimicry, identifying a novel mechanism of viral evasion from host cell defenses.